The The Development Strategies for National Economies after the Covid-19 Pandemic - Fedirko, Olha; Zatonatska, Tetiana (Ekonomika, 2020)
What are the economy sectors will help countries overcome the crisis caused by the COVID-19 pandemic? How countries should rezone their investment strategies to bolster recovery in main economy sectors? Using the Cobb-Douglas model, the importance of agriculture, energy, education, and ICT industries for GDP growth was proven. It was confirmed that agriculture and industry will be key sectors in the post-crisis period for Ukraine, Poland and Austria. During the time of economic uncertainty growth, ICT and e-commerce sectors are principal tools that will sustain the population’s well-being.